Uncovering Trends in Psychological Empowerment: Empowering Insights Through Comprehensive Exploration and Advanced Data Analysis - Fika Wulan Meilana Putri; Sri Handari Wahyuningsih (Riviera Publishing, 2026)
This research aims to analyze trends in psychological empowerment, particularly in companies engaged in the technology industry, innovation, start-ups, creative industries, employee development, and customer service-oriented sectors. Companies such as Google, Apple, Airbnb, Pixar, Deloitte, Zappos, Ritz-Carlton, and Southwest Airlines have demonstrated that psychological empowerment plays an important role in improving service quality, reducing workplace stress, and fostering a positive work culture all of which contribute to the long-term success of an organization. This research employed a qualitative method with a bibliometric analysis approach. Data were sourced from Scopus using the keyword